2004
DOI: 10.1111/j.0014-3820.2004.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Phenotype, Mating Behavior, and Fitness of Queens in the Ant Lasius Niger

Abstract: Abstract. Considerable attention has focused on why females of many species mate with several males. For social hymenopteran insects, efforts have primarily concentrated on determining whether multiple mating increases colony performance due to the increased genetic diversity. Most of these studies are correlative because it is difficult or impossible to experimentally mate queens in most species. Thus, the positive associations found between multiple paternity and colony fitness in some cases may not be due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 74 publications
(70 reference statements)
3
31
1
Order By: Relevance
“…To our knowledge, whether egg-laying rate is positively associated with queen mating frequency has not been studied in social insects. The finding that mating status of queens was not associated with head size or initial body weight contrasts with the results of Fjerdingstad & Keller (2004), who reported a positive relationship between queen phenotype and mating behaviour. In their study, heavier queens of L. niger at the time of mating flights were more likely to mate with several males.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, whether egg-laying rate is positively associated with queen mating frequency has not been studied in social insects. The finding that mating status of queens was not associated with head size or initial body weight contrasts with the results of Fjerdingstad & Keller (2004), who reported a positive relationship between queen phenotype and mating behaviour. In their study, heavier queens of L. niger at the time of mating flights were more likely to mate with several males.…”
Section: Discussioncontrasting
confidence: 99%
“…Our genetic analyses are consistent with previous studies showing that L. niger queens can mate with up to four males during large-scale mating flights (Boomsma & van der Have 1998;Fjerdingstad et al 2002;Fjerdingstad & Keller 2004). We found a positive association between queen mating frequency and apportionment of maternity at the time of emergence.…”
Section: Discussionsupporting
confidence: 92%
“…Queens of all species were of unknown age, and their mating frequency was not determined. Nevertheless, genetic analyses previously showed that queens of L. humile mate once (monandry) (Krieger and Keller, 2000), while queens of L. niger (Boomsma and Van der Have, 1998;Fjerdingstad and Keller, 2004) and P. pygmaea (Trontti et al, 2007) can mate multiply (polyandry). No information is currently available on queen mating frequency for Tapinoma erraticum and Crematogaster scutellaris.…”
Section: Methodsmentioning
confidence: 99%
“…A usual method consists in dissecting the spermatheca and dispersing sperm cells in a physiological buffer (usually saline) solution, and then counting samples of sperm suspension in aliquots placed in a cell count chamber (e.g., hemacytometers, Makler chamber) under a microscope (Duchateau and Mari n, 1995;Boomsma, 1997, 1998;Fjerdingstad and Keller, 2004;Keller and Passera, 1992;Stein et al, 1996;Tschinkel 1987;Woyciechowski and Krol, 1996). The method can be refined by marking sperm cells with a fluorescent DNA-staining solution (e.g., Hoechst; Sakaluk and O Day, 1984) and counting under a microscope equipped for epifluorescence microscopy, eventually after fixation in glacial acetic acid (Wiernasz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cofounding queens that anticipate queen elimination may therefore invest less in reproduction than singly founding conspecifics, a prediction that has found empirical support (Bernasconi & Strassmann 1999;Cahan 2001). However, abstaining from reproduction is costly to all individuals in the colony because the survival probability of incipient colonies is positively related to the number of workers (Adams & Tschinkel 1995;Sommer & Hö lldobler 1995;Fjerdingstad & Keller 2004). We therefore expect that queens may be able to (i) assess the quantity of developing brood and the number of cohabiting queens, and (ii) adjust their reproductive effort according to the amount of brood, but only when competing queens are present.…”
Section: Introductionmentioning
confidence: 99%